Feminist Hermeneutical Imagination: A Study on Sue Monk Kidd’s The Book of Longings (International Journal of Food and Nutritional Sciences, 2022)
Sue Monk Kidd’s The Book Of Longings, takes a remarkable journey through the lens of feminist hermeneutical imagination. This paper explores the profound impact of the imaginative approach in reinterpreting historical narratives and empowering women’s voices within the context of biblical stories. Through the protagonist Ana, a fiercely independent and intellectually curies woman, Kidd challenges traditional interpretations of biblical texts and presents a fresh perspective of the lives of women during that time. Ana’s longing for knowledge, her unyielding spirit, and her desire to be heard become a catalyst for feminist hermeneutics to unfold. By empowering feminist hermeneutical imagination, Kidd not only highlights the agency and resilience of women, but also sheds light on their untold stories and contributions. The paper celebrates the transformative power of feminist interpretation, not only within literature but also in shaping our understanding of gender dynamics and social justice. It emphasizes the importance of diverse perspectives and the need to challenge traditional narratives to create a more inclusive and equitable world. The Book Of Longings serves as a testament to the enduring power of feminist hermeneutical imagination, inspiring readers to embrace their own voices and rewrite the narratives that silenced women throughout history.